Pengaruh Pelatihan Quantum Learning Terhadap Minat Belajar Ilmu Pengetahuan Alam Pada Siswa Sekolah Dasar - Nadea Zulfa Khairunnosa; R Rachmy Diana (Universitas Islam Indonesia, 2018)
This study aims to examine the influence of quantum learning training on increasing interest in science learning to students. Subjects in this study were 8 students of class IV SD Negeri Ponjong II Gunungkidul Daerah Istimewa Yogyakarta with less learning interest in science subject. The data was analized by a scale of interest in learning science subject with GUTMANN scale model compiled by researchers. Experimental designed employed was pretest – posttest control group design. Subject in this study was randomly divided in two group, experiment group and control group that consist of 4 subjects in each groups. Mann Whitney U was used to analize the differences between the pretest, posttest, and follow up from gained score. The result of score analysis pretest – posttest was 0,021 and pretest – follow up score was 0,020 ( p < 0,05), mean rank of experiment group was 6,50 and mean rank of controlt group was 2,50 which indicated that experiment group has a higher level of interest in learning science. This showed that quantum learning training could increase student’s interest in learning science subject at SD Negeri Ponjong II Gunungkidul Daerah Istimewa Yogyakarta.